2022
DOI: 10.5603/dk.a2022.0045
|View full text |Cite
|
Sign up to set email alerts
|

Foot Care Performance and Foot Self-Care Behaviors in Iranian Patients with Type 2 Diabetes: A Cross-Sectional Study

Abstract: Objective: A diabetic foot ulcer is one of the preventable complications of diabetes that can lead to amputation, morbidity, and mortality and increase treatment costs. This study aimed to investigate the relationship between self-care behaviors, demographic-clinical variables and, foot care performance in patients with diabetes. Materials and methods: This descriptive-analytical study was performed on 191 patients with type 2 diabetes in Asadabad (Hamadan province) in 2021. The demographic-clinical informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Our findings revealed that patients who reported having diabetes for more than 10 years had higher odds of good foot care behaviors. This is consistent with other studies 45 , 46 and might be explained by prolonged exposure to the disease, which can increase patients’ experience and improve self‐care behaviors and knowledge. 47 However, these results are controversial, with other studies showing that foot care performance declines with the increasing duration of diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings revealed that patients who reported having diabetes for more than 10 years had higher odds of good foot care behaviors. This is consistent with other studies 45 , 46 and might be explained by prolonged exposure to the disease, which can increase patients’ experience and improve self‐care behaviors and knowledge. 47 However, these results are controversial, with other studies showing that foot care performance declines with the increasing duration of diabetes.…”
Section: Discussionsupporting
confidence: 93%